BIO-PHYSIOLOGICAL EFFECTS OF LD50 OF CRUDE VENOM OF BLACK PAKISTANI COBRA (Naja Naja karachiensis) IN MICE - Z. Riaz; M. Q. Zaman; Z. Ullah; Habib-ur-Rehman; M. S. Yousaf; I. Rabbani; M. I. Khan; M. S. Hussain; S. Tahir; K. A. Majeed (Journal of Animal and Plant Sciences, 2015)
The present study evaluated the acute bio-physiological effects of Lethal dose 50 (LD 50) of crude venom of Black Pakistani Cobra, Naja naja karachiensis, collected from Southern Punjab, Pakistan. Adult mice (n=20) were injected intramuscularly with normal saline (n/s) or LD50 of crude venom (1.2mg/kg). Blood was collected by cardiac puncture after anesthesia at intervals 0 (n/s), and 1, 1.5, 2 (LD50 venom) hours. Complete blood count, glucose, serum Alanine aminotransferase (ALT), albumin, total proteins and urea were measured to assess the physiology. One way ANOVA was used to analyze the data (P<0.05). A significant increase in erythrocyte count, its indices and thrombocytosis was observed during the study. Leukocyotsis was observed after a transient leucopenia at 1 hour post envenomation. No significant difference was observed for lymphocytes and monocytes. Serum concentrations of urea, total proteins, albumin and ALT were also increased significantly with all time intervals. Hypoglycemia was observed initially followed by hyperglycemia at 1.5 and 2 hours. The changes indicate that venom has severe hemotoxic potential and disrupts physiological processes by affecting vital organs like kidneys and liver in mice.
Keywords: Cobra venom; Hematology; Bio-physiological effects; Lethal dose 50; Mice